1999
DOI: 10.1128/jvi.73.1.819-825.1999
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of a Bovine Enteric Calicivirus: Relationship to the Norwalk-Like Viruses

Abstract: Jena virus (JV) is a noncultivatable bovine enteric calicivirus associated with diarrhea in calves and was first described in Jena, Germany. The virus was serially passaged 11 times in colostrum-deprived newborn calves and caused diarrheal disease symptoms at each passage. The complete JV genome sequence was determined by using cDNA made from partially purified virus obtained from a single stool sample. JV has a positive-sense single-stranded RNA genome which is 7,338 nucleotides in length, excluding the poly(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
83
0
5

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(90 citation statements)
references
References 45 publications
(40 reference statements)
2
83
0
5
Order By: Relevance
“…In recent years, genomic data has been obtained from the two viruses, Bo/Jena/80/DE and Bo/New-bury2/76/UK, and these strains were assigned into the prototype bovine NoVs (BNoVs) of genotype 1 (GIII-1) and genotype-2 (GIII-2) within GIII, respectively. Further isolates of the genotype 1 or genotype 2 BNoVs have been identified in the United Kingdom, The Netherlands, and United States (Liu et al, 1999;Oliver et al, 2003Oliver et al, , 2004Smiley et al, 2003;van der Poel et al, 2003;Wise et al, 2004), which have confirmed the existence of the two distinct genotypes.…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…In recent years, genomic data has been obtained from the two viruses, Bo/Jena/80/DE and Bo/New-bury2/76/UK, and these strains were assigned into the prototype bovine NoVs (BNoVs) of genotype 1 (GIII-1) and genotype-2 (GIII-2) within GIII, respectively. Further isolates of the genotype 1 or genotype 2 BNoVs have been identified in the United Kingdom, The Netherlands, and United States (Liu et al, 1999;Oliver et al, 2003Oliver et al, , 2004Smiley et al, 2003;van der Poel et al, 2003;Wise et al, 2004), which have confirmed the existence of the two distinct genotypes.…”
Section: Introductionmentioning
confidence: 68%
“…and 84.3-89.8% aa identity. In addition, the GIII-1 BNoV strains, one Korean strain Bo/MA88/KOR and one German strain (Bo/Jena/DE; Liu et al, 1999), showed a low aa identity with the human sapovirus (SaV) (24.1%), BEC-NBV (18.5%), rabbit hemorrhagic disease virus (RHDV) (21.3%), and feline calicivirus (FCV) (27.8%) strains, whereas there was slightly higher aa identity with the human GI, GII and GIV NoV (56.5-72.2%), porcine GII-2 NoV (59.3-60.2%), and murine GV NoV (50.0-50.9%) strains. The GIII-2 strains (Bo/MA88/KOR and Bo/Jena/DE) also had a low aa identity with the human SaV (22.2-23.1%), BEC-NBV (17.6-18.5%), RHDV (22.2-23.1%), and FCV (25.9%) strains, whereas there was slightly higher aa identity with the human GI, GII and GIV NoV (53.7-75.0%), porcine GII-2 NoV (56.5-60.2%), and murine GV NoV (52.8-54.6%) strains.…”
Section: Genetic Diversity Of Bnovsmentioning
confidence: 99%
See 1 more Smart Citation
“…The NB2 and JV were identified by EM in the faeces of diarrhoeic calves in 1978 in Great Britain (Woode and Bridger, 1978) and in 1980 in Germany (Gunther and Otto, 1987). They were later genetically identified as belonging to the genus Norovirus (Liu et al, 1999;Oliver et al, 2003) where all BoNoV strains fall into the genogroup III . Two genotypes are described in the BoNoV genogroup: viruses genetically related to JV were assigned to the genotype 1 and viruses genetically related to NB2 to the genotype 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the human viruses, they have not been well characterised, in part due to the lack of a cell culture system and the apparently low numbers of particles in faeces. Two of the three reported bovine viruses, one from the UK (Newbury agent 2, NA2) [7] and one from Germany (Jena virus) [8], were shown recently to be members of the family Caliciviridae. In the present paper, we characterise the second bovine enteric calici-like virus, Newbury agent 1 (NA1), identi¢ed in the UK to examine the hypothesis that NA1 is also a member of the family Caliciviridae and to explore its relationship to NA2.…”
Section: Introductionmentioning
confidence: 99%